Ã£Æâ¢Ã£ÆÂ©Ã£ÆÆÃ£âÂ·Ã£ÆÂ¥Ã£âÂ«Ã£ÆÂ¼Ã£Æâ°Ã£ÂÂ§Ã¦Â¼Â¢Ã¥ÂâÃ¯Â¼ËÃ§â Å¸Ã¨ÂªÅ¾Ã¯Â¼â°Ã£ÂÂ®Ã¨Â¦Å¡Ã£ÂËÃ¦âÂ¹ Ã¯Â¼ËUSING FLASHCARDS TO MEMORIZE THE KANJI JUKUGOÃ¯Â¼â° - Prasetiani, Dyah (Faculty of Languages Ã¢â¬â¹Ã¢â¬â¹and Arts, State University of Semarang, 2013)
Learning kanji is generally difficult for the Japanese learners because its figure, stroke order, and pronounce (onyomi and kunyomi) are difficult to remember. Moreover, every object in the world is presented by kanji. Thus, practically there are large in numbers of kanji. Remembering all the kanji and also the jukugo is not easy. Most of the students may easily forget it soon after they learn it. Therefore, they have to find effective, fun, and easy learning methods to improve their ability in mastering kanji. The bottom line is that they must consistently review the kanji they have learned to ensure that they would never-ever forget them. Otherwise, no matter how memorable the kanji are, they make up its nature to start forgetting and lose track of them once they start learning their 500th kanji and beyond. Flashcards could be a good solution to overcome the problem. It could help students consistently review the kanji, especially the jukugo.